Validasi Perangkat Self Assessment dan Peer Review dalam Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) - Hajiriah, Titi Laily (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2022)
This study aims to measure the feasibility level of peer review and self-assessment development tools by implementing them into Numbered Head Together (NHT) type cooperative model learning. The feasibility of the device can be interpreted through the validation of 2 experts based on the truth of the content, language, language, and readability. In addition, the feasibility of this device is assessed directly by 10 students based on the learning results they get and their response to the given learning device.. This research is a 4D learning model development study that was piloted using the One Group Pretest-Posttest Design technique. The trial was conducted after the learning device that had been developed obtained a score as a device that is very suitable to be applied to high school students in grade XI on excretion system material with an average percentage of both validators of 96%, and 100% of the response of students who have used these devices. The implementation of measures in rpp reached 100% with the reliability of both observers reaching 96.21%. Classical completion was obtained by 80% with the achievement of learning goals reached 81.25%, while for the transformation of Peer Review and Self Assessment assessment into learning outcomes supported by assessments from teachers are homogeneous with a strong correlation with a correlation value of 0.75. Based on the results of the research obtained, it can be concluded that peer review and self assessment can be transformed into the form of learning outcomes that aim to strengthen the assessment of teachers through the application of Numbered Head Together (NHT) type cooperative model learning devices that are worth using with good learning outcomes.